Estudo da viabilidade de formação de nitreto de boro em aços inoxidáveis ferríticos - Santos, Ellen Rodrigues dos (Universidade Federal de São Carlos, 2020)
Since the 90s, the petroleum industry has been conducting research on alloys that are wear and corrosion resistant once several equipment parts used in the oil exploitation, extraction and production, such as pipes, joints, valves and pumps, are subjected to severe wear and corrosion conditions. Recently, the research group of DEMa-UFSCar has been developing different metallic materials presenting high wear and corrosion resistance for coating applications. An example of such developed materials are the boron-modified stainless steels. Supermartensitic, ferritic and duplex stainless steels with variation of boron content between 0,3% and 3,5% wt were developed. These materials were able to maintain the excellent corrosion resistance of stainless steels, while increasing the wear resistance to values much higher than those of usually presented by conventional stainless steels. This project proposes the development of chemistry composition and processing scheme of a ferritic stainless steel modified with boron and nitrogen aiming the in-situ formation of hexagonal boron nitride during the solidification process. The hexagonal boron nitride is a self-lubricating phase, which allows a remarkable friction reduction and optimized anti-wear property due to the presence of M2B and M3B2 borides types. The alloy selection for this study was based on results of thermodynamic calculations with the aid of the CALPHAD Method supported by Thermo-Calc software TCFE7 database. Three compositions of 444 ferritic stainless steel modified with different amounts of boron and nitrogen were obtained, one by spray forming and two by conventional casting. The produced deposit and ingots were characterized by different techniques such as X-ray diffraction (XRD), optical microscopy (OM), scanning electron microscopy (SEM), and X-Ray Dispersive Energy Spectroscopy (EDS).
Feasibility study of the boron nitride formation in ferritic stainless steel
Keywords: Aço Inoxidável Ferrítico; Boro; Conformação por Spray; Fundição; Nitreto de Boro; Ferritic Stainless Steel; Boron; Spray Forming; Casting; Boron Nitride; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA